2016
DOI: 10.1016/j.brat.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion enhances the efficacy of explicit cognitive reappraisal as an emotion regulation strategy in individuals with major depressive disorder

Abstract: Cognitive reappraisal has been shown to be an effective strategy to regulate depressed mood in healthy and remitted depressed individuals. However, individuals currently suffering from a clinical depression often experience difficulties in utilizing this strategy. Therefore, the goal of this study was to examine whether the efficacy of explicit cognitive reappraisal in major depressive disorder can be enhanced through the use of self-compassion and emotion-focused acceptance as preparatory strategies. Thereby,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 77 publications
1
59
0
2
Order By: Relevance
“…Thus, interventions supporting patients to recognize and understand the effects of emotions on body processes might be helpful to augment cognitive‐behavioural therapy in hypochondriasis. Besides a classical cognitive‐behavioural therapy approach with psychoeducation aiming at a profound knowledge of physiological correlates of emotions, as well as situation analyses to understand emotion body symptom cascades, mindfulness‐ and acceptance‐based strategies seem promising regarding the improvement of emotional awareness, identification and differentiation of emotions (Baer, Smith, & Allen, ; Hill & Updegraff, ), and might even facilitate adaptive emotion regulation (Diedrich, Hofmann, Cuijpers, & Berking, ; Erisman & Roemer, ). In this context Kleinstäuber, Gottschalk, Berking, Rau, and Rief (), recently conducted a multi‐centre study investigating the beneficial effect of enriching cognitive‐behavioural therapy for patients with somatic symptom disorder (including patients that would have been diagnosed with hypochondriasis according to DSM‐IV) with emotion regulation strategies focusing on mindfulness‐ and acceptance‐based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interventions supporting patients to recognize and understand the effects of emotions on body processes might be helpful to augment cognitive‐behavioural therapy in hypochondriasis. Besides a classical cognitive‐behavioural therapy approach with psychoeducation aiming at a profound knowledge of physiological correlates of emotions, as well as situation analyses to understand emotion body symptom cascades, mindfulness‐ and acceptance‐based strategies seem promising regarding the improvement of emotional awareness, identification and differentiation of emotions (Baer, Smith, & Allen, ; Hill & Updegraff, ), and might even facilitate adaptive emotion regulation (Diedrich, Hofmann, Cuijpers, & Berking, ; Erisman & Roemer, ). In this context Kleinstäuber, Gottschalk, Berking, Rau, and Rief (), recently conducted a multi‐centre study investigating the beneficial effect of enriching cognitive‐behavioural therapy for patients with somatic symptom disorder (including patients that would have been diagnosed with hypochondriasis according to DSM‐IV) with emotion regulation strategies focusing on mindfulness‐ and acceptance‐based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using this paradigm provide preliminary evidence that the ability to compassionately support oneself in distressing situations might be more effective than established strategies (such as reappraisal) in more severely depressed patients [46]*]. Moreover, these studies provide preliminary evidence that self-compassion might facilitate the subsequent utilization of strategies that have been shown to be effective but that patients often find difficult to apply (such as reappraisal [47]). M a n u s c r i p t ART 6 3.…”
Section: Page 5 Of 18mentioning
confidence: 96%
“…This study suggested that deliberately activating feelings of self‐compassion (i.e., using self‐compassion as a form of emotion regulation) was more effective than a simple waiting period in reducing depressed mood following a mood induction but did not differ significantly from either acceptance or reappraisal. In a second study, conducted concurrently with the work reported here, this group considered the relationship between emotion regulation and the ability of depressed patients to benefit from a cognitive reappraisal exercise following mood induction (Diedrich, Hofmann, Cuijpers, & Berking, ). This study randomized participants to complete a negative mood induction followed by a preparatory acceptance induction, self‐compassion induction, or a waiting period, and then a period of cognitive reappraisal, with mood changes over the course of the experimental procedure as the outcome measure.…”
Section: Introductionmentioning
confidence: 99%